Evaluate the Protective Effect of Lactobacillus against Collateral Damage Induced by Ciprofloxacin and Levofloxacin in Iraqi Patients - Ali F. Hassan; Suha N. Muhsin (College of Pharmacy University of Baghdad, 2019)
Abstract:                                                                                                                Fluoroquinolones drugs are an important class of wide spectrum antibacterial agents, and active against a wide range of Gram-negative and Gram-positive pathogens, are divided into four generations. Collateral damage is a term used to refer to ecological adverse effects of antibiotic therapy, occurring as drug-resistant organisms and the unwanted development of colonization or infection with multidrug-resistant organisms. This damage is mostly related to levofloxacin and Ciprofloxacin.  Aim: The aim of the current study was to compare the incidence of collateral damage between two quinolone antibiotic derivatives (ciprofloxacin and Levofloxacin) and evaluate the activity of lactobacillus to reduce the collateral damage. Patients and Methods: This study was carried out on 100 patients. Administration of ciprofloxacin, levofloxacin each alone or in combination with lactobacillus, the character of diarrhea and grade of diarrhea was studied before and after 10 days of administration each dosing protocol. Results: there are a significant increase in the incidence of diarrhea for all groups when compare between before and after treatment diarrhea, Number of patients with diarrhea in group 1 after finish the treatment was not significantly higher when compared with group 2 (p>0.05) meanwhile number of patients with diarrhea in group 4 after finish the treatment was significantly lower when compared with group 3 (p>0.05). Conclusion; The use of ciprofloxacin and levofloxacin associated with incidence of collateral damage represented as diarrhea and levofloxacin is the least risk of this damage, and using of lactobacillus with levofloxacin was better results than the other three groups.